Manajemen Proyek Sistem Informasi untuk Efisiensi Usaha Jasa Laundry - Chairil Surya Pratama; Yahfizham (Journal Of Informatics And Busisnes, 2024)
Big businesses are not the only ones in the business world that benefit from technology. big companies. Information and communication technology (ICT)-driven Micro, Small, and Medium-Sized Enterprises (MSMEs) will simplify operations and increase productivity. In this instance, information and communication technology will simplify, expedite, and improve the dependability of company. Laundry services, for instance, are frequently located, particularly in close proximity to workplaces or universities. The washing services that are provided are likewise rather varied; some employ package delivery services or pick-up and delivery services. cleaning. Customers frequently complain about having too little time to do their laundry. laundry, with the sophistication of information and communication technology, everything that needs to be instantaneous and quick in the laundry process. When used to its full potential, today's sophisticated information and communication technology, including the internet, can improve washing process efficiency. When used effectively, the internet may improve customer experiences, expedite customer activities, and raise the value of laundry liberty in online enterprises. online business, use the laundry application media to support customer activities and ensure customer happiness.